Analysis of the main trends published on TikTok during the quarantine period by COVID-19 - Francisco José Olivares García; Inés Méndez Majuelos (Universidad Carlos III de Madrid, 2020)
Introduction: TikTok has been one of the most used social networks by younger users during confinement by COVID-19. Objective: To analyze the main trends and videos published on the platform during the quarantine period. Methodology: The main contents and trends published on TikTok were analyzed during 25 days of confinement from April 9 to May 3, 2020. It is presented a qualitative and quantitative analysis of viral trends and challenges related to COVID-19. Results: The study presents a completely new content generation and viralization model, based on the presentation of content that, apparently, is not useful, does not change the world or the lives of citizens, and presents empty products and based exclusively on fun and imitation. Conclusions: In front of the actions generated in other networks making face masks and protection screens, TikTok has only provided humor and entertainment. However, under an apparent layer of superficiality and frivolity, you can discover a picture of our society behind closed doors.